2009
DOI: 10.1246/cl.2009.600
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Crystal Structure, and Solid-state Fluorescence of a CH2Cl2-solvated Crystal of 6,13-Bis(t-butylphenyl)-2,3,9,10-tetrapropoxypentacene

Abstract: Slow evaporation of 6,13-bis(t-butylphenyl)-2,3,9,10-tetrapropoxypentacene in CH2Cl2 solution in the dark, yielded CH2Cl2-solvated single crystals easily. The crystals were characterized by X-ray analysis and solid-state fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[4] In recent years, we have prepared various alkyl‐substituted tetracenes and we found that, as expected, the introduction of alkyl side‐chains into the tetracene framework facilitated their solubility in common organic solvents (even pure n ‐hexane), as well as providing relatively low melting points (about 100 °C). [5] During the course of this work, we observed a most‐interesting and unexpected result: the color of these materials in the solid state differed for compounds with different alkyl side‐chains. Specifically, in the solid‐state, the materials ranged in color from yellow to red, whereas in solution, they were all orange.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…[4] In recent years, we have prepared various alkyl‐substituted tetracenes and we found that, as expected, the introduction of alkyl side‐chains into the tetracene framework facilitated their solubility in common organic solvents (even pure n ‐hexane), as well as providing relatively low melting points (about 100 °C). [5] During the course of this work, we observed a most‐interesting and unexpected result: the color of these materials in the solid state differed for compounds with different alkyl side‐chains. Specifically, in the solid‐state, the materials ranged in color from yellow to red, whereas in solution, they were all orange.…”
Section: Introductionmentioning
confidence: 88%
“…In particular, in the series of 1,4,7,10‐tetraalkyl‐ ( 1 – 6 ) and 1,4,7,10‐tetraisoalkyltetracenes ( 7 – 9 ), a small change in the substituent could cause considerable changes in the solid‐state color. For example, in the tetraalkyl series,[5b] the methyl‐, propyl‐, and pentyl derivatives ( 1 , 3 , and 5 ) were orange, the ethyl derivative ( 2 ) was yellow, the hexyl derivative ( 6 ) was red, and the butyl derivative ( 4 ) was a mixture of yellow and red, both of which could be separated. [5a] In this sequence, the number of carbon atoms in the alkyl substituent correlated with color as follows: compounds 2 and 4 were yellow solids, compounds 1 , 3 , and 5 were orange solids, and compounds 4 and 6 were red solids.…”
Section: Crystallochromy Of Alkyl‐substituted Tetracenesmentioning
confidence: 99%
See 3 more Smart Citations